Maternal Hypotension during Fetoscopic Surgery: Incidence and Its Impact on Fetal Survival Outcomes. (21st October 2013) - Ngamprasertwong, Pornswan; Habli, Mounira; Boat, Anne; Lim, Foong Yen; Esslinger, Hope; Ding, Lili; Sadhasivam, Senthilkumar
Abstract : In this retrospective cohort study, we aimed to determine the incidence of intraoperative maternal hypotension during fetoscopic surgery for twin-twin transfusion syndrome (TTTS) and to evaluate the impact of intraoperative hypotension on fetal survival. A total of 328 TTTS patients with recipient twin cardiomyopathy who underwent fetoscopic surgery under epidural anesthesia were included. The exposure of interest was maternal medical therapy with nifedipine for the treatment of fetal cardiomyopathy. We found that intraoperative hypotension occurred in 53.4% (175/328 patients). There was no statistically significant difference in incidence of hypotension between nifedipine exposure and nonexposure groups (54.8% versus 50.8%, P = 0.479 ). However, the nifedipine exposure group received a statistically significant higher dose of phenylephrine (7.04 ± 6.38 mcg/kg versus 4.70 ± 4.14 mcg/kg, P = 0.018 ) and higher doses of other vasopressor, as counted by number of treatments (6.06 ± 4.58 versus 4.96 ± 3.42, P = 0.022 ). There were no statistically significant differences in acute fetal survival rate (within 5 days) and fetal survival rate at birth between hypotensive and nonhypotensive patients. We concluded that preoperative exposure to nifedipine resulted in increased intraoperative maternal vasopressor requirement during fetoscopic surgery under epidural anesthesia. In patients who had intraoperative maternal hypotension, there was no correlation between the presence of maternal hypotension and postoperative fetal survival.